Ancora una nota su Eusebio di Vercelli - Simonetti, Manilo (Augustinianum, 2012)
Responding to a publication on the Latin versions of the corpus Athanasianum, the author of this note returns to the debate concerning the Ps-Athanasian de trinitate and rejects the hypothesis which holds that Eusebius of Vercelli inspired this theological tract in order to make Athanasius appear more credible in the West as a teacher of orthodoxy.